Strategy for Maximizing Customer Lifetime Value: A Study on Fairness Cream Users of Bangladesh - Ahmed, Fayez; Kamal, Mohammad Afsar (Journal of Business and Technology (Dhaka), 2014)
Customer lifetime value is one of the most important concepts in marketing on which lots of scholarly writings have been done to analyze this concept. In this study, we have used this concept to study fairness cream market of Bangladesh. Through this study we have tried to find out the factors that increase customer lifetime value in fairness cream market. To conduct the study, we have used simple random sampling technique where 300 respondents have been interviewed. We have utilized multiple regression technique to analyze the data. The findings that have been generated from the analysis is that fairness cream companies can increase customer usage months of fairness cream product or customer lifetime value through proper application of three factors which are creating fear that experimentation may be dangerous for skin, strong positioning that users brand is the best brand in the market and marketers brand has international recognition. DOI: http://dx.doi.org/10.3329/jbt.v8i1-2.18286 Journal of Business and Technology (Dhaka) Vol.8(1-2) 2013; 63-78